2021
DOI: 10.1016/j.bioactmat.2020.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous incorporation of PTH(1–34) and nano-hydroxyapatite into Chitosan/Alginate Hydrogels for efficient bone regeneration

Abstract: Tissue regeneration based on the utilization of artificial soft materials is considered a promising treatment for bone-related diseases. Here, we report cranial bone regeneration promoted by hydrogels that contain parathyroid hormone (PTH) peptide PTH(1–34) and nano-hydroxyapatite (nHAP). A combination of the positively charged natural polymer chitosan (CS) and negatively charged sodium alginate led to the formation of hydrogels with porous structures, as shown by scanning electron microscopy. Rheological char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 67 publications
2
33
0
Order By: Relevance
“…Chitosan (CS) is a copolymer of D-glucosamine and N-acetyl-D-glucosamine [116]. Due to its biodegradable, non-toxic, antibacterial and biocompatible properties, CS can be used as a scaffold material or growth factor carrier in bone tissue engineering, and has attracted much attention [117,118]. Unfortunately, pure chitosan scaffolds have poor mechanical properties, and lack osteoconductivity.…”
Section: Hydroxyapatite/chitosan (Ha/cs) Compositementioning
confidence: 99%
“…Chitosan (CS) is a copolymer of D-glucosamine and N-acetyl-D-glucosamine [116]. Due to its biodegradable, non-toxic, antibacterial and biocompatible properties, CS can be used as a scaffold material or growth factor carrier in bone tissue engineering, and has attracted much attention [117,118]. Unfortunately, pure chitosan scaffolds have poor mechanical properties, and lack osteoconductivity.…”
Section: Hydroxyapatite/chitosan (Ha/cs) Compositementioning
confidence: 99%
“…In fact, the 1–34 amino acid fragment of PTH (PTH(1–34), also known as teriparatide), is the active sequence responsible for the bone remodeling function of PTH [ 88 ] and it has been approved for its use as an osteoanabolic drug in the clinical treatment of bone defects, such as osteoporosis [ 89 ]. PTH(1–34) along with nano-HA (nHA) and hydrogel combinations (to emulate the natural structures of bone) have been integrated to facilitate osteogenic differentiation of BM-MSCs [ 90 ]. The nanofibers and porous structure of the Gel-nHA-PTH scaffolds enhanced cell adhesion and showed good binding with bone tissue.…”
Section: Strategies Promoting Bone Healing Through An Endogenous Responsementioning
confidence: 99%
“…Moreover, the mature collagen component can be stained red by Masson's to assess the maturity of the new bone tissue. [ 36 ] From Figure 9b, it is intuitively observed that the regenerated new bone treated with PTBSK presented a layer‐by‐layer structure with the largest red area, indicating the formation of mature bone tissue in the bone defect. The quantitative results are shown in Figure 9d, after 8 weeks, the mature bone area of PTBSK was 26.33 ± 1.32%, which was significantly higher than 22.11 ± 1.61% of PTB and 17.32 ± 0.99% of PB ( p < 0.01), indicated that the synergistic effect of the calcium‐binding peptide and the shish‐kebab structure could greatly promote the regeneration of mature bone.…”
Section: Resultsmentioning
confidence: 99%